Comparative Study between Subcostal Transversus Abdominis Plane Block Analgesia and Epidural Analgesia in Upper Abdominal Surgeries - Hazem Moawad; Mohamed Makharita; Abdelrahman Elnaggar; Mohamed Eloraby (International Journal of Medical Arts, 2022)
Background: Subcostal transversus abdominis plane [TAP] block is a peripheral nerve block that provide effective analgesia after upper abdominal surgery. Epidural analgesia is considered the gold standard of analgesia but not suitable for all patients. The Aim of The Work:  In this study we compared the efficacy of subcostal TAP analgesia, to epidural analgesia in major upper abdominal surgeries.Patients and Methods: Eighty-four patients allocated into two groups [42 patients in each]: epidural group [Group E] and subcostal TAP group [group S]. Patients in both groups received preoperative bolus dose of 10 ml bupivacaine 0.5% plus 100 mg magnesium sulphate in 20 ml normal saline and received postoperative infusion of 20 ml bupivacaine 0.5% plus 100 mg magnesium sulphate in 50ml saline at a rate 6 ml/hour for 72 hours. The primary outcome was the total postoperative morphine consumption. Secondary outcomes were time to the first rescue analgesia, pain score at rest and cough, hemodynamic changes, postoperative sedation score and adverse effects.Results: There was significant increase in total postoperative morphine consumption in group S [9.51 ± 6.46] compared to group E [4.77 ± 3.74] [P < 0.001]. There was significant increase in pain score in group S compared to group E during rest and cough postoperatively at all time periods.  Sedation score is significantly higher in group E rather than group S.Conclusion: Epidural analgesia and subcostal TAP catheter infusion analgesia, both provide adequate postoperative analgesia in favor of epidural analgesia, but subcostal TAP avoids major drawbacks of epidural analgesia. Hence, subcostal TAP catheter may be an effective alternative to epidural catheter for providing postoperative analgesia after major upper abdominal surgeries.